Prediction of Endometrial Pathology by Endometrial Cut-Off Thickness in Patients with Abnormal Uterine Bleeding - Nazia Sajjad, Jehangir Kazi, Salma Zaman (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determinecut-off endometrial thickness for prediction of endometrial pathology in patients with abnormal uterine bleeding. Study design: Cross-sectional study Place and duration of study: Department of Obstetrics & Gynaecology, Niazi Medical & Dental College, Sargodha from 1st October 2021 to 30th September 2022. Methodology: Seventy perimenopausal women who were above the age of 40 years and were suffering from acute urinary bleeding were enrolled. Transvaginal ultrasound was conducted. Uterus as well as adnexa were scanned longitudinally ad transversally. Doppler was activated and hemodynamic-parameters were bilaterally examined from the main dominant uterine arteries branch to the cervical-corporal section of uterus. Endometrial vessels color flow examination detected number, size, as well as vessel regularity of branching. Three different vascular patterns were observed. Results: The mean age of the women in Group I was 44.25 ± 2.69 years where as in Group II cases it was mean 47.16 ± 3.25 years. Transvaginal ultrasound endometrial thickness cut-off was determined as >10.5mm. Comorbidities were higher in the Group II with neoplastic changes observed. The value of obesity, age, hypertension and diabetes as well as endometrial thickness >10.5 were significantly higher in mltivariant analysis whereas age, obesity and ET>10.5 was increased in the univariate analysis as well. Transvaginal ultrasound-endometrial thickness >10.5mm was having highest value of sensitivity and specificity Conclusion: Perimenopausal women suffering with abnormal uterine bleeding should undergo histopathological examination if they have a transvaginal ultrasound-endometrial thickness value greater than 10.5mm.The main risk factors towards increased risk of endometrial pathology development are age and obesity. Keywords: Abnormal uterine bleeding, Endometrial carcinoma, Histopathology